PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS APLIKASI ANDROID UNTUK SISWA KELAS X SEKOLAH MENENGAH ATAS PADA MATERI NILAI PERBANDINGAN TRIGONOMETRI - Afri, Lusi Eka; Alfarizi, Muhamad; Annajmi, Annajmi (Jurnal Edu Research, 2023)
This study aims to produce a valid learning media based on Android App on trigonometric ratio values material. The type of research used is research and development, which consists of four stages of development of the definition (Define), the design (Design), development (Develop) and Desseminate (Desseminate). However, this research the development stage, this is due to limitid time and energyfor further research. The instrument used in this study was a validation questionnaire sheet. Based on the results of the validity test of android app based mathematics learning media that has been carried out by 2 validators, the average score of the android app based mathematics learning media validity results is 3,61 with a very valid category. So it can be concluded that the android app based mathematics learning media is very valid.